Targeted next generation sequencing of mucosal melanomas identifies frequent NF1 and RAS mutations - Cosgarea, Ioana; Utikal, Jochen; Schadendorf, Dirk; Roesch, Alexander (OncoTarget, 2017)
Oncotarget | https://doi.org/10.18632/oncotarget.16542 Ioana Cosgarea, Selma Ugurel, Antje Sucker, Elisabeth Livingstone, Lisa Zimmer, Mirjana Ziemer, Jochen Utikal, Peter Mohr, Christiane Pfeiffer, Claudia...